2017
DOI: 10.1007/s11764-017-0611-6
|View full text |Cite
|
Sign up to set email alerts
|

Ambulant monitoring and web-accessible home-based exercise program during outpatient follow-up for resected lung cancer survivors: actual use and feasibility in clinical practice

Abstract: PurposeThe aim of this study is to evaluate the feasibility of a telehealthcare application for operable lung cancer (OLC) patients, consisting of ambulant symptom and physical activity monitoring (S&PAM) and a web-accessible home-based exercise program (WEP), and identify possible barriers for successful adoption and implementation.MethodsA two-stage mixed methods design was used, in which 22 OLC patients and their treating healthcare professionals (HCPs) participated from pre-surgery to three (stage 1; n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 38 publications
(42 reference statements)
1
64
0
Order By: Relevance
“…PCRPs delivered through practical avenues such as print materials, telephone counseling, and web-based programs are an alternative [125][126][127][128][129] for patients with fewer visits to the cancer center. Web-based PCRPs with online encouragement, online diaries, and online physical activity programs proved to be feasible with median vigorous PAU over time, and the burden for HCPs appeared to be limited [130][131][132].…”
Section: Determinantsmentioning
confidence: 99%
“…PCRPs delivered through practical avenues such as print materials, telephone counseling, and web-based programs are an alternative [125][126][127][128][129] for patients with fewer visits to the cancer center. Web-based PCRPs with online encouragement, online diaries, and online physical activity programs proved to be feasible with median vigorous PAU over time, and the burden for HCPs appeared to be limited [130][131][132].…”
Section: Determinantsmentioning
confidence: 99%
“…eHealth in lung cancer patients is a relatively new occurence, and few studies have been published. Most of these studies are related to symptom monitoring [ 7 , 8 , 10 , 11 ], which is very different from our multicomponent intervention. One study by Gustafson et al [ 9 ] reported the results of a trial in which they compared the use of a comprehensive online intervention (Comprehensive Health Enhancement Support System [CHESS]) with standard Internet access in palliative lung cancer patients and especially their caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts et al [5] also conclude that improved understanding of strategies for enhancing patient engagement with digital interventions to help maintain adherence is necessary. This is a salient issue within the exercise intervention feasibility studies provided by Timmerman et al [6] (lung cancer survivors) and Harder et al [7] (breast cancer survivors) where the value of putting patient user input at the centre of the design and assessment of digital interventions is clearly demonstrated. We are pleased to include these studies as they also reveal the extent of developmental work required to design and implement electronically supported interventions.…”
Section: Improving Survivor Outcomesmentioning
confidence: 99%